The Implementation of Song Technique in Teaching English for Junior High School Students - Maherni, Ni Kadek Dian; Ratminingsih, Ni Made (Universitas Pendidikan Ganesha, 2021)
The study aimed to: (1) describe the implementation of song technique in teaching English for Junior High School students in SMPN 2 Kubutambahan and; (2) find out teachersâ€™ reasons in implementing song technique for teaching English Junior High School students at SMPN 2 Kubutambahan. The study was qualitative research which employed case study design. The subjects were two English teachers in SMPN2 Kubutambahan that was chosen through purposive sampling technique. The instruments were human instrumen, observation sheet and interview guide. The data were collected by note-taking, observation and interview. The collected data have analysed through data analysis method which consisted of data reduction, data display and conclusion drawing. The results show that: (1) the observed teachers implemented song technique using general syntaxwith other teachers for instance, choosing the proper song, selecting suitable activities, making quiz and providing homework, but in various ways, and; (2) there were several reasons for why the observed teachers implementing song technique i.e. enjoyable, motivating, attractive and vocabulary enhancement factors. Therefore, it could be concluded that even though the English teachers implemented the technique in general syntax, but still there are some variations that teachers applied and they have some important reasons in implementing this technique for teaching English.Â